DESIGN AND FATIGUE ANALYSIS OF SUBMERGED PIPELINE IN EAST JAVA SEA - GUSTI BAGUS YOGA P (NIM : 15514036), I
Improvement on oil and gas distribution caused submerged pipeline technology becomes the most efficient technology to distribute oil and gas. During the operation period, submerged pipeline will be subjected to cyclic loading. Therefore, in order to ensure the ability of submerged pipeline to withstand the load, design of the submerged pipeline and fatigue analysis on submerged pipeline must be performed. In this study, analysis of pipeline wall thickness, analysis of on-bottom stability, analysis of pipeline installation, analysis of pipeline free span, fatigue analysis, and ultimate limit state (ULS) analysis will be performed. The output of this study is the pipeline wall thickness, the pipeline concrete coating thickness, the laybarge configuration during the pipeline installation, the pipeline allowable free span, and the fatigue life of the submerged pipeline.